Herman Hochstadt [Singapore, Permanent Secretary in Civil Service] - Hochstadt, Herman (Institutional Knowledge at Singapore Management University, 2015)
Herman Hochstadt's name is synonymous with the Singapore civil service, having helmed several ministries as Permanent Secretary. He tells DNA what it was like working with the founding fathers of modern Singapore and shares that successful leaders need to have "the devil in them".